Sebaceous carcinoma of forehead: a rare malignant lesion - Mujahid, Abdul Malik; Ul Abidin, Zain; Ilyas, Asma; Khalid, Farrukh Aslam; Yousaf, Muhammad Amin; Tarar, Moazzam Nazeer (Journal of the Pakistan Medical Association, 2022)
Sebaceous carcinoma is an uncommon malignant tumour of the sebaceous glands. This lesion typically occurs as painless and slow growing nodule in the eyelid region. In rarity, it can develop on buccal mucosa, head and neck, and other regions of the body in people in their 60s and 70s. Sebaceous carcinoma is locally aggressive and carries the potential of regional and distant spread. We present the case of a 15-year-old male who was diagnosed with sebaceous carcinoma over the forehead. After discussing the case in the board meeting, surgery was performed to remove the tumour with 1cm margin. Outer table of the frontal bone was also removed and intraoperative frozen section was done for margin clearance. After the Figure 1excision, soft tissue coverage was done with free Anterolateral thigh flap and the patient received six cycles of post-operative radiation therapy.